ANÁLISE DE VIABILIDADE TÉCNICA E ECONÔMICA ENTRE VEÍCULOS A COMBUSTÃO INTERNA E VEÍCULOS ELÉTRICOS - Fabrício Cristiano Pangoni (2024)
Electric vehicles have been identified as one of the ways to reduce environmental impact and global warming. However, the exchange of technologies also depends on the consumer's economic criteria. Therefore, the objective of this work is to contribute to consumer savings and sustainability by replacing internal combustion vehicles with electric vehicles powered by renewable photovoltaic generation. For this, technical and economic analysis was used comparing the use of internal combustion vehicles and electric vehicles in four cases according to their categories: Case 1 the Fiat Mobi Like and JAC e-JS1 subcompacts; Case 2 the compact Hyundai HB20 Sense and Peugeot E-208 GT; Case 3 the midsize Nissan Versa Sense and BYD Dolphin GS 180EV; Case 4 for the large Nissan Leaf Tekna and Toyota Corolla Cross XR 20. 3 scenarios were used in which the daily distance traveled was 10%, 50% and 100% of the electric vehicle's autonomy. The use of gasoline fuels (Hypothesis 1) and ethanol (Hypothesis 2) is still considered for combustion vehicles and for electric vehicles the use of electrical energy from the dealership (Hypothesis 3) and with the installation of a system are considered. grid-connected photovoltaic system (SFVCR) (Hypothesis 4) for a residence in the city of Campo Grande - MS for a period of 96 months, starting in August 2023. For technical feasibility, the sizing of the SFVCR was carried out, the analysis of the residence's electrical installations for the installation of the charging station, with demand analysis, protections, electrical panel and sizing of the circuit that will energize the station. The costs for the SFVCR, charging station, vehicles and the residence were calculated. Finally, an economic feasibility study was carried out using the Net Present Value (NPV) for all cases and finally the mileage at which the electric vehicle is more viable than the internal combustion vehicle was determined. As a result, the analysis concluded that they presented the following order of best investments, for Scenario 1 of Cases 1, 2, 3 and 4: Hypothesis 2, Hypothesis 1, Hypothesis 4 and Hypothesis 3. For Scenario 2 of Cases 1, 2 and 4: Hypothesis 2, Hypothesis 1, Hypothesis 4 and Hypothesis 3. For Case 3 the following order: Hypothesis 4, Hypothesis 3, Hypothesis 2 and Hypothesis 1. For Scenario 3 of Cases 1 and 4: Hypothesis 4, Hypothesis 2 , Hypothesis 1 and Hypothesis 3. For Case 2: Hypothesis 2, Hypothesis 1, Hypothesis 4 and Hypothesis 3. For Case 3: Hypothesis 4, Hypothesis 3, Hypothesis 2 and Hypothesis 1. Thus, this essay demonstrated that in each category researched, the viability of electric vehicles is conditioned on the daily distance traveled so that their operating cost compensates for the higher cost of purchasing the vehicle compared to internal combustion vehicles.